The physics of meaning: More than inhuman? - Hartley John (Cultural Science)
The ambition of this paper is to say that if “cultural science” accepts the need to rethink culture along scientific rather than just critical lines, then at the same time physics must rethink its own commitment to “culture-free” methodology. That has only yielded what we might call “meaningless universe theory,” without addressing ways that physics as a discourse is strongly marked by culture, with the usual signs of gender, race, and hegemony present in its methods. It needs to take responsibility for applications of its discoveries that enter the cultural sphere only to threaten its total annihilation. An alternative to meaninglessness might be to take more seriously the marginalized and derided cultures of everyday thinking, as is attempted by Bogna Konior, and for physics-as-a-discipline to join the effort to reform science. If self-criticism is good for the cultural goose, then it’s good for the scientific gander; and a “cultural science” should say so. Since physics is the most scientific and least cultural of the sciences, this paper uses it as a limit case of knowledge realism. I argue that a science of culture requires reform of the ideology and applications of science as well as new models of culture.